1)
A = 4 * y - 2 * y
A = 4y - 2y
A = 2y
B= - 5a * 6a
B= - 30a²
C= - 5a + 6a²
D= n + n + n + n * n
D= n² + 3n
2)
E= (5x - 6) - (4 - 5x)
E= 5x - 6 - 4 + 5x
E= 10x - 10
F= - (7x² + 6x) + (- 5 + x²)
F= - 7x² - 6x - 5 + x²
F= - 6x² - 6x - 5
3)
E= - 3(2x + 5)
E= - 6x - 15
F= 4a(6 - a)
F= 24a - 4a²
G= 7(- x + 2) + 3(2x - 7)
G= - 7x + 14 + 6x - 21
G= - x - 7
H= (x + 2)(x + 3)
H= x² + 3x + 2x + 6
H= x² + 5x + 6
K= (x - 2)(x - 6)
K= x² - 6x - 2x + 12
K= x² - 8x + 12
L= (2x + 4)(4 - 3x)
L= 8x - 6x² + 16 - 12x
L= - 6x² - 4x + 16
4)
1 - C
2 - D
3 - A
4 - B